2013
DOI: 10.1186/1756-9966-32-34
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Fluorodeoxyglucose accumulation as a biological marker of hypoxic status but not glucose transport ability in gastric cancer

Abstract: BackgroundThe use of [18F] 2-fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET) for detection of gastric cancer is often debated because FDG uptake varies for each patient. The purpose of this study was to clarify the molecular mechanisms involved in FDG uptake.Material and methodsFifty patients with gastric cancer who underwent FDG-PET and gastrectomy were studied. Snap-frozen tumor specimens were collected and examined by real-time PCR for relationships between maximum standardized uptake value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…Our results were similar to those of other studies in which 18 F-FDG uptake did not correlate with GLUT-1 [43, 44], or HIF-1α expression [45]. However, other studies demonstrated that 18 F-FDG uptake was correlated with HIF-1α [46], and GLUT-1 expression [45].…”
Section: Discussionsupporting
confidence: 91%
“…Our results were similar to those of other studies in which 18 F-FDG uptake did not correlate with GLUT-1 [43, 44], or HIF-1α expression [45]. However, other studies demonstrated that 18 F-FDG uptake was correlated with HIF-1α [46], and GLUT-1 expression [45].…”
Section: Discussionsupporting
confidence: 91%
“…In gastric cancer, the frequency of GLUT1 expression has been reported to vary between 16.9% and 60% (15-17,31). There have been only a few studies on GLUT1 expression and 18 F-FDG avidity in gastric cancer (15,17,32). Consistent with our current study, Yamada et al reported that GLUT1-positive tumor cells were significantly associated with 18 F-FDG avidity (17).…”
Section: Discussionsupporting
confidence: 81%
“…However, Takebayashi et al did not find any correlation between the standardized uptake value of primary gastric cancer and GLUT1 expression. Those authors reported hypoxiainducible factor 1a to be another potential clinicopathologic parameter for 18 F-FDG avidity in gastric adenocarcinomas (32).…”
Section: Discussionmentioning
confidence: 99%
“…A study on gastric cancer demonstrated the relationship between T stage and SUV max (15), and another study showed the correlation between the maximal diameter of primary lesion and SUV max . In the latter study, messenger RNA level of hypoxia-inducible factor 1 a was also correlated with SUV max ; therefore, they suggested the mechanism that growth-related hypoxia induces anaerobic glycolysis and increases glucose metabolism (16).…”
Section: Discussionmentioning
confidence: 79%